2004
DOI: 10.1111/j.0906-6705.2004.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐MSH reduces the internalization of Staphylococcus aureus and down‐regulates HSP 70, integrins and cytokine expression in human keratinocyte cell lines

Abstract: Alpha-melanocyte-stimulating hormone (alpha-MSH) is a neuropeptide predominantly produced by the pituitary gland, but it is also generated by many extra-pituitary cells including keratinocytes of the skin. This neuropeptide has anti-inflammatory and antimicrobial effects and probably contributes in innate immunity. Staphylococcus aureus is the aetiological agent of a wide range of infections in humans. Colonization of human skin by S. aureus is a characteristic feature of several skin diseases and is often fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Our results showed that PGA-α-MSH down-regulated IL-6, TGF-β, and TNF-α expression induced by Pg- LPS stimulation in EC and FB cultures. Similar results have been demonstrated in vitro studies with human bronchial epithelial cells, pre-stimulated with Pg -LPS [21] or on fibroblasts, pre-stimulated with E. Coli -LPS [11] and with keratinocytes activated by S. aureus [31]. These data showed the anti-inflammatory properties PGA-α-MSH in gingival cells and that this effect was time dependent and appeared more efficient in FB than in EC.…”
Section: Discussionsupporting
confidence: 82%
“…Our results showed that PGA-α-MSH down-regulated IL-6, TGF-β, and TNF-α expression induced by Pg- LPS stimulation in EC and FB cultures. Similar results have been demonstrated in vitro studies with human bronchial epithelial cells, pre-stimulated with Pg -LPS [21] or on fibroblasts, pre-stimulated with E. Coli -LPS [11] and with keratinocytes activated by S. aureus [31]. These data showed the anti-inflammatory properties PGA-α-MSH in gingival cells and that this effect was time dependent and appeared more efficient in FB than in EC.…”
Section: Discussionsupporting
confidence: 82%
“…The sequence of this neuropeptide is Ac-Ser-Tyr-Ser-Met-Glu-His-Phe-Arg-TrpGly-Lys-Pro-Val-NH 2 . It controls inflammation and high temperature through immunomodulation, downregulates several proinflammatory cytokines, and stimulates production of antiinflammatory cytokines such as interleukin-10 (IL-10) (2,14,23). The widespread distribution of this peptide and its receptor in many barrier cells such as keratinocytes and in various immune cells suggests its potential role in host defense.…”
mentioning
confidence: 99%
“…In the case of α-MSH, the indirect antibacterial effects are connected with multiple general anti-inflammatory properties. For example, in human keratinocytes α-MSH down-regulates β-1 integrins and heat shock surface protein 70, both of which are essential molecules in the invasion of keratinocytes by S. aureus [103]. Furthermore α-MSH down-regulates pro-inflammatory cytokine expression in human keratinocytes suggesting it has a protective role in both infection and inflammation [103].…”
Section: Therapeutic Potential In the Light Of In Vivo Studiesmentioning
confidence: 99%
“…For example, in human keratinocytes α-MSH down-regulates β-1 integrins and heat shock surface protein 70, both of which are essential molecules in the invasion of keratinocytes by S. aureus [103]. Furthermore α-MSH down-regulates pro-inflammatory cytokine expression in human keratinocytes suggesting it has a protective role in both infection and inflammation [103]. It is therefore tempting to speculate that taken together these data suggest a relationship between resolution of infection in vivo and the presence of action of NPs.…”
Section: Therapeutic Potential In the Light Of In Vivo Studiesmentioning
confidence: 99%